PENGEMBANGAN MATERI GEOGRAFI INTEGRASI PEMANASAN GLOBAL (GLOBAL WARMING) DENGAN METODE PROBLEMBASED LEARNING PADA KELAS XI DI SMA N 1 SURUH (JPP, 2011)
Inserting global warming material in the Geography curriculum subjects and the applicationof suitable learning mode is the right step to provide an understanding of globalwarming and education to the students to take an active role in preventing it as well ashaving concern for the creation of a green environment, having an awareness of environmentalsustainability and sustainable development. This study is in the form of Researchand Development. It is preceded by the development of the learning instructionsof Geography’s integration of global warming with Problem Based Learning’s approachand tested on control and experimental classes. Data is taken with the observation, questionnairesand tests. The Methods of data analysis is using percentage of score descriptions.Problem-solving capabilities are analyzed parametrically by using T test. Thi researchhas given results to the global warming learning material which consist of syllabuswith 35.6 average score with very good criteria, Lesson Plan with 36 average scorewith very good score, Student book with 33.6 average score with very good criteria, studentworksheet with 35 score with very good criteria so that the teaching and learninginstructions is very good to teach global warming materials. Problem Based Learningteaching method is more effective, students are more active and.Keywords: Geography Material Development, Global Warming, Problem BasedLearning